The Triple Helix Model for the Conceptual Mechanism of Cooperation between Higher Education and Business: The Regional Aspect - Baimuratov, Uraz B.; Zhanbayev, Rinat A.; Sagintayeva, Saule S. (Economy of Regions, 2020)
Single-industry regions, common to all industrially developed countries, need to overcome the economic crises. We assume that it is possible to achieve this goal based on new forms of cooperation between the main participants: business, state, education, and science. Based on the triple helix model, the study develops a mechanism for cooperation between higher education and business in depressed single-industry regions. The model was tested on the example of the Republic of Kazakhstan. We use the methodological principles of logical, statistical analysis and synthesis. To increase the impact of universities on the national economic growth, we propose a cooperation mechanism based on the Triple Helix model. This model is adapted to the specificity of single-industry and depressed regions, where regional universities play a dominant role as a source of innovation and innovative synergy for the cooperation of partners involved. Simultaneously, the creation of new forms of cooperation between higher education and business leads to the acceleration of social and economic development of regions. The mechanism of the proposed triple helix model aims to encourage all participants to generate innovations, provide high-quality educational services, conduct research and fill business orders. Local and state authorities in the field of economic management can use the results and conclusions of the survey for creating regional development programmes.